EFEKTIFITAS SERTIFIKAT ELEKTRONIK DALAM MENCEGAH TERBITNYA SERTIFIKAT HAK ATAS TANAH GANDA - Satriani Satriani (Institut Agama Islam Negeri Fattahul Muluk Papua, 2026)
The issue of duplicate certificates remains a serious issue in the Indonesian land system, often leading to land ownership disputes and causing both material and immaterial losses to legitimate land rights holders. This circumstance shows that the traditional land registration system still has a number of flaws, including administrative chaos, a lack of integration of land data, and the possibility of mistakes in the process of measuring and registering land. In order to enhance the land registration system and avoid duplicate certificates, the government is implementing electronic land certificates as part of a digital revolution in the land sector. The objectives of this study are to examine the laws governing digital land registration, evaluate how well electronic certificates work to stop duplicate certificates from being issued, and pinpoint institutional and normative barriers to their use in providing legal protection for landowners. Through the examination of several primary and secondary legal sources, this study employs normative legal research methodologies or library legal research with a statutory and conceptual approach. The findings demonstrate that the use of electronic certificates has the potential to improve the land registration system's efficacy through the integration of national land databases, enhancing the system's transparency, bolstering the security of land documents, avoiding duplicate land registration, and enhancing the accuracy and efficiency of land services. Its implementation is nevertheless hampered by a variety of issues, including insufficient technical infrastructure, uneven human resource capacity, and the need for more public participation and digital literacy. Therefore, to guarantee the best possible implementation of electronic certificates, offering legal certainty and protection for land rights holders, regulatory strengthening, institutional capacity building, fair distribution of technology capabilities and infrastructure, and public outreach are required.